2018
DOI: 10.1002/jcp.27715
|View full text |Cite
|
Sign up to set email alerts
|

Expression of novel proteins by polyomaviruses and recent advances in the structural and functional features of agnoprotein of JC virus, BK virus, and simian virus 40

Abstract: Polyomavirus family consists of a highly diverse group of small DNA viruses. The founding family member (MPyV) was first discovered in the newborn mouse in the late 1950s, which induces solid tumors in a wide variety of tissue types that are the epithelial and mesenchymal origin. Later, other family members were also isolated from a number of mammalian, avian and fish species. Some of these viruses significantly contributed to our current understanding of the fundamentals of modern biology such as transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 195 publications
(363 reference statements)
3
26
0
Order By: Relevance
“…Our results also shed new light on previous reports on BKPyV agnoprotein and the closely related JCPyV and SV40 homologues (Gerits and Moens, 2012;Saribas et al, 2018): These include facilitating polyomavirus replication (Ng et al, 1985), increasing viral late phase production (Carswell et al, 1986) and plaques size (Hou-Jong et al, 1987), acting as egress factor (Panou et al, 2018) or as viroporin (Suzuki et al, 2010). We demonstrate that mitochondrial fragmentation occurs not only for BKPyV strains carrying an archetype NCCR, but also for the human JCPyV or the monkey SV40 supporting the view that this dramatic agnoprotein-mediated function is evolutionary conserved across different species, cell types and hosts.…”
Section: Innate Immune Sensors Have Been Characterized In Primary Humsupporting
confidence: 84%
“…Our results also shed new light on previous reports on BKPyV agnoprotein and the closely related JCPyV and SV40 homologues (Gerits and Moens, 2012;Saribas et al, 2018): These include facilitating polyomavirus replication (Ng et al, 1985), increasing viral late phase production (Carswell et al, 1986) and plaques size (Hou-Jong et al, 1987), acting as egress factor (Panou et al, 2018) or as viroporin (Suzuki et al, 2010). We demonstrate that mitochondrial fragmentation occurs not only for BKPyV strains carrying an archetype NCCR, but also for the human JCPyV or the monkey SV40 supporting the view that this dramatic agnoprotein-mediated function is evolutionary conserved across different species, cell types and hosts.…”
Section: Innate Immune Sensors Have Been Characterized In Primary Humsupporting
confidence: 84%
“…VP 4 seems to facilitate the lytic release of the SV40 virions (24), but a recent study demonstrated that VP4 is not required for this process (25). The agnoprotein controls the perinuclear localization of VP 1 during virion formation, which then triggers virion assembly (26). In total, SV40 translates for nine proteins.…”
Section: Sv40 Genomic Organizationmentioning
confidence: 99%
“…The early regulatory proteins of JCV tumor antigens, LT-Ag and Sm t-Ag, are produced by the alternative splicing of the viral early transcripts [ 13 ] ( Figure 3 A). Both play critical roles in the viral life cycle [ 48 , 72 , 92 , 143 , 144 , 145 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of additional human polyomaviruses has been recently facilitated due to availability of the new technologies, including the rolling circle amplification and digital transcriptome subtraction. The current number of human polyomavirus has now risen to 14 [ 13 , 14 ]. Note that not every isolated human polyomavirus was proven to be associated with any particular human disease.…”
Section: Introductionmentioning
confidence: 99%